2001
DOI: 10.1038/sj.onc.1205092
|View full text |Cite
|
Sign up to set email alerts
|

Id proteins in cell cycle control and cellular senescence

Abstract: The Id family of helix ± loop ± helix (HLH) proteins are thought to a ect the balance between cell growth and di erentiation by negatively regulating the function of basic ± helix ± loop ± helix (bHLH) transcription factors. Although it has been suggested for some time that Id is involved in cell cycle regulation, little is known about the molecular mechanism of this control. Recent studies, however, have revealed that Id binds to important cell cycle regulatory proteins other than bHLH proteins. Two such prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
177
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 112 publications
7
177
0
2
Order By: Relevance
“…Among them, SERPINB4 had the highest overexpression with 126-fold difference from nonlesional skin. Other DEGs such as ID1, ID4, KRT16 and HMOX1, which have been previously indicated in psoriasis disease (Hanselmann et al, 2001;Leigh et al, 1995;Ronpirin et al, 2010;Ruchusatsawat et al, 2011;Zebedee et al, 2001) were also identified in the present study.…”
Section: Figsupporting
confidence: 84%
“…Among them, SERPINB4 had the highest overexpression with 126-fold difference from nonlesional skin. Other DEGs such as ID1, ID4, KRT16 and HMOX1, which have been previously indicated in psoriasis disease (Hanselmann et al, 2001;Leigh et al, 1995;Ronpirin et al, 2010;Ruchusatsawat et al, 2011;Zebedee et al, 2001) were also identified in the present study.…”
Section: Figsupporting
confidence: 84%
“…During the early phase of TGF-␤ activation, ID3 and RGS1 were the most highly up-regulated genes in M2 IL-4/dex . ID3 is a known negative transcriptional regulator of the basic helix-loop-helix (bHLH) family that inhibits other bHLH transcription factors (42). ID3 has complex function in the immune and vascular systems including support of B cell immunity, dendritic cell differentiation, and angiogenesis (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway information was derived from the Signal Transduction Knowledge Environment (stke. sciencemag.org), the Kyoto Encyclopedia of Genes and Genomes (http://www.genome.jp/kegg), and the following references: Ishitani et al, 1999;Lundberg and Weinberg, 1999;Sakamuro and Prendergast, 1999;Taguchi et al, 2000;Shaulian and Karin, 2001;Zebedee and Hara, 2001;Hyodo-Miura et al, 2002;Schneider et al, 2002;Yamagishi et al, 2002;Bracken et al, 2003;Polager and Ginsberg, 2003;Williams et al, 2003;Wu et al, 2003;Campos et al, 2004;Einarson et al, 2004;Li and Guan, 2004;Rubin and Atweh, 2004;Wada and Penninger, 2004;Sasahira et al, 2005. Of particular interest was a strong increase in the expression of WNT inhibitors in SCLC cells, namely NLK, SOX11, and TCF4.…”
Section: Regions Of Differencementioning
confidence: 99%